Removal of organic dye from aqueous solution by adsorption on sawdust - Alam, Md. Zahangir; Muyibi, Suleyman Aremu (2003)
Studies on the removal of organic dye (methylene blue) by adsorption on sawdust (SD) as low-cost absorbent were carried out. The effect of various experimental parameters such as contact time, initial concentration (dye), initial pH, dose and particle size of absorbent was investigated by following a batch adsorption technique. The percentage removal of dye increased with the decrease in initial dye concentration, particle size of absorbent, and increase in contact time, pH of the dye solution, and dose of absorbent. An initial pH in the range of 5-7 was effective for the dye removal (98%) by the absorbent. The absorbent SD was shown to be promising material for removal of organic dye from aqueous solution.